LncRNA TMPO antisense RNA 1 promotes the malignancy of cholangiocarcinoma cells by regulating let-7g-5p/ high-mobility group A1 axis. Issue 2 (1st February 2022) - Chang, Hongbin; Yao, Yixin
ABSTRACT: Cholangiocarcinoma (CHOL) is often diagnosed at an advanced stage; therefore, exploring its key regulatory factors is important for earlier diagnosis and treatment. This study aimed to identify the mechanisms of long non-coding RNA (lncRNA) TMPO Antisense RNA 1 (TMPO-AS1), microRNA let-7 g-5p, and high-mobility group A1 (HMGA1) proteins in CHOL. Our results, through quantitative real-time PCR and Western blot detection, showed that TMPO-AS1 and HMGA1 were overexpressed while let-7 g-5p was underexpressed in CHOL. Cell function experiments in CHOL cells revealed that TMPO-AS1 knockdown inhibited cell proliferation, colony formation, and cell migration, but induced apoptosis. TMPO-AS1 knockdown also suppressed tumor growth in vivo. Together with luciferase assay and Western blotting, we found that TMPO-AS1 could sponge let-7 g-5p to promote HMGA1 expression. Moreover, HMGA1 overexpression attenuated the effect of TMPO-AS1 downregulation in CHOL cells. Overall, our findings identified the oncogenic effect of TMPO-AS1 on CHOL cells, which may put forward a novel methodology for CHOL diagnosis and therapy. Graphical abstract: uf0001